2017
DOI: 10.1371/journal.pone.0162045
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Epistasis on Growth in an Erhualian × White Duroc Pig Cross

Abstract: Epistasis describes an interaction between the effects of loci. We included epistasis in quantitative trait locus (QTL) mapping of growth at a series of ages in a cross of a Chinese pig breed, Erhualian, with a commercial line, White Duroc. Erhualian pigs have much lower growth rates than White Duroc. We improved a method for genomewide testing of epistasis and present a clear analysis workflow. We also suggest a new approach for interpreting epistasis results where significant additive and dominance effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Epistatic interactions between genes for some quantitative traits, such as meat quality (Ovilo et al, 2002;Duthie et al, 2011a), carcass (Duthie et al, 2010), reproductive traits (Bidanel, 1993;Rodríguez et al, 2005;Noguera et al, 2009), growth (Crooks and Guo, 2017), and muscle fiber traits (Estellé et al, 2008) have been reported for pigs. These findings shed light on the different interactions underlying the genomic regulation in several traits.…”
Section: Introductionmentioning
confidence: 99%
“…Epistatic interactions between genes for some quantitative traits, such as meat quality (Ovilo et al, 2002;Duthie et al, 2011a), carcass (Duthie et al, 2010), reproductive traits (Bidanel, 1993;Rodríguez et al, 2005;Noguera et al, 2009), growth (Crooks and Guo, 2017), and muscle fiber traits (Estellé et al, 2008) have been reported for pigs. These findings shed light on the different interactions underlying the genomic regulation in several traits.…”
Section: Introductionmentioning
confidence: 99%
“…However, and to the best of our knowledge, this is the first empirical study to reveal epistatic regulation of a quantitative trait in Atlantic salmon. Epistasis-influences on growth have been documented in other animals such as mice [10], chicken [51] and pigs [52]. The documentation of epistasis as a genetic basis for quantitative trait variation in Atlantic salmon could have implications for selective breeding programs; a topic that has been debated in both MAS [53] and GS [54].…”
Section: Evidence Of Epistasis and Its Practical Implicationsmentioning
confidence: 99%